Feasibility of Same-Day Discharge After Appendectomy in Pediatric Patients: A Systematic Review and Meta-Analysis - Zheng, Yifei; Qi, Shiqin (Frontiers in Pediatrics, 2022)
Background: To compare the readmission rate, rate of urgent/unplanned visits to emergency, complication rate along with cost of health care among children and adolescents who were discharged the same day following a laparoscopic appendectomy and those who were not discharged on the same day. Methods: A systematic search was performed in the PubMed, Embase, and Scopus databases. Randomized controlled trials and studies, observational in design, were considered for inclusion. The included studies were conducted in children and adolescents with uncomplicated appendicitis undergoing laparoscopic appendectomy and compared outcomes of interest between patients that were discharged the same day (SDD group) following the operation and patients that were discharged within 2 days post-operatively (non-SSD group). Statistical analysis was performed using STATA software. Effect sizes were reported as pooled odds ratio (OR) or weighted mean difference (WMD) with 95% confidence intervals. Results: A total of 13 studies with 32,021 children and adolescents were included. There was no significant difference in the risks of unplanned visit to the emergency department (OR 1.07, 95% CI: 0.78, 1.47), readmission (OR 0.83, 95% CI: 0.66, 1.05), reoperation/re-intervention (OR 1.73, 95% CI: 0.19, 16.2) and complications (OR 0.84, 95% CI: 0.67, 1.06) in both groups of patients. Patients in the SDD group had slightly lower risk of wound infection/complication (OR 0.74, 95% CI: 0.57, 0.96) compared to patients in the non-SDD group. Those with SDD had to incur comparatively lesser hospital expense (in USD) compared to those with no SDD (WMD -2587.4, 95% CI: -4628.3, -546.6) Conclusion: In children and adolescents with uncomplicated acute appendicitis undergoing laparoscopic appendectomy, same-day discharge is not associated with increased readmission risk, unplanned visits to emergency, and complications. Further, SDD is associated with lower cost of hospital care. Adoption of SDD in this subset of children and adolescents may be encouraged.